Peningkatan Kompetensi Guru Melalui Pelatihan Penyusunan Modul Digital di SMP Kecamatan Dewantara Kabupaten Aceh Utara - Mahsa, Masithah; Pratiwi, Rani Ardesi; Trisfayani, Trisfayani; Rahayu, Ririn; Ukhra, Aura Radhuatul; Ramadhana, Tri Wahyu (Universitas Islam Negeri Sumatera Utara, 2023)
There are many obstacles teachers face in the learning process, such as inappropriate teaching materials, limited face-to-face time, and the large amount of material that must be completed, means that teachers must be smart in developing teaching materials that are interesting, interactive and in line with students' needs. The aim of this activity is to overcome these obstacles through training in preparing digital modules using the canva application at the Junior High School Dewantara North Aceh so that the learning process runs optimally. The participants in this activity were teachers at SMPN 1 Dewantara, SMPN 2 Dewantara and SMPN 3 Dewantara. Meanwhile, the methods used are presentation, practical and dialogical methods. The presentation method is used to convey theories about using the canva application. Then, a practical method was carried out by involving participants directly to apply the canva application in compiling digital modules. Meanwhile, the dialogic method is applied to discuss problems experienced by participants during the training. Based on the activities that have been carried out, the following results were obtained: (1) teachers at Junior High School Dewantara were able to install the canva application on their devices; (2) teachers at Junior High School Dewantara are able to compose digital modules using the canva application; (3) increasing the competence of teachers at Junior High School Dewantara in the field of technology; and (4) encourage student enthusiasm in the learning process.